Percepção da qualidade de vida em idosos com e sem a presença de sintomas depressivos - Simone Lima de Macedo (2006)
The concerning to guarantee one a better quality of life to the final years appeared as a consequence of the population aging. The depression is still a source of controversy in literature and it is gradually not seen as a normative phenomenon of the aging process but starts being seen as a change in the course of the normal development. In this sense the interest on investigating the perception of the quality of life in aged appears. However, the literature directed to this subject frequently investigates institutionalized aged people or the ones who look for health care, and they do not consider aged from all different aged groups, usually generating tendentious results in favor of the depression, negative ones for the quality of life and lack of definition related to the behavior of these variables when the age and other sociodemographic variables are considered. The aims of this work were to evaluate the perception of the quality of general life and specific domains of the brief Whoqol, considering aged with and without depressive symptoms evaluated by the CES-D and to investigate the possible influence of sociodemographic variables in a resident communitarian sample in the city of Juiz de Fora, MG belonging to the project PENSA of the UFJF. The results had pointed that the average of age of the sample was 73,37 years (DP = 8,57) formed by 73,6% of women, married aged people (49.0%) and up to seven years of study (56.1%). From 369 citizens, 36.9% presented depressive symptoms, adopting to the CES-D the cut-off point of ¡Ý11 validated for the aged Brazilian population resident in the community. Both the perception of the general quality of life as well as specific domains were different and statistically significant in both groups (aged with and without depressive symptoms). When taken in consideration the sociodemographic variables, there were also statistically significant differences between the two groups for: gender, age, numbers of years of study and income. The logistic multiple regression for the CES-D pointed that the main explanatory variables of the model had been gender (2,884), the domain 3, of the social relations (0,979), the domain 2 or Psychological domain (0,931) and the general issue of quality of life (0,946). One concludes that the feminization of the old age people is a reality for the sample in question and that the women present more depressive symptoms that the men. The perception of the quality of life in all domains and the two general questions are modified in the presence of depressive symptoms. Taking in consideration the sociodemographic variables, the perception of the quality of life is also modified, being the perception in the general question of quality of life and in the physical, environmental and social relations domains for the aged ones without depressive symptoms; and in the issue of general health and the environmental domain for the aged ones with depressive symptoms. Finally, gender, the general question of quality of life and the psychological and social relations domains were the most related ones to the presence of depressive symptoms.